Low Roll‐Off Perovskite Quantum Dot Light‐Emitting Diodes Achieved by Augmenting Hole Mobility. (4th March 2020) - Wang, Yu; Teng, Yu; Lu, Po; Shen, Xinyu; Jia, Pei; Lu, Min; Shi, Zhifeng; Dong, Bin; Yu, William W.; Zhang, Yu
Abstract: The external quantum efficiencies (EQEs) of perovskite quantum dot light‐emitting diodes (QD‐LEDs) are close to the out‐coupling efficiency limitation. However, these high‐performance QD‐LEDs still suffer from a serious issue of efficiency roll‐off at high current density. More injected carriers produce photons less efficiently, strongly suggesting the variation of ratio between radiative and non‐radiative recombination. An approach is proposed to balance the carrier distribution and achieve high EQE at high current density. The average interdot distance between QDs is reduced and this facilitates carrier transport in QD films and thus electrons and holes have a balanced distribution in QD layers. Such encouraging results augment the proportion of radiative recombination, make devices with peak EQE of 12.7%, and present a great device performance at high current density with an EQE roll‐off of 11% at 500 mA cm −2 (the lowest roll‐off known so far) where the EQE is still over 11%. Abstract : A reduction of the average interdot distance among perovskite QDs enhances the transport of carriers and forms a more balanced distribution of electrons and holes in QD layer. This suppresses Auger recombination and boosts the external quantum efficiency of the devices up to 12.7%. An 11% efficiency roll‐off is obtained at 500 mA cm −2 .